2010
DOI: 10.1002/ptr.2903
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effect of tea polyphenols on local tissue damage induced by snake venoms

Abstract: The methanolic extract of fresh tea leaves of Camellia sinensis L. (Theaceae) (CS) was assayed for its potential to inhibit enzymes with hydrolytic activity in Naja naja kaouthia Lesson (Elapidae) and Calloselasma rhodostoma Kuhl (Viperidae) venoms. These snake venom enzymes are responsible for the early effects of envenomation, such as local tissue damage and inflammation. The CS extract inhibited phospholipase A(2), proteases, hyaluronidase and L-amino acid oxidase in both venoms by in vitro neutralization a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(29 citation statements)
references
References 29 publications
0
29
0
Order By: Relevance
“…Moreover, given the promising bioactivity of fraction F5, in the characterization of the major compounds by GC-MS it was relevant to find two phenolic compounds in the derivatized fraction F5, namely protocatechuic acid, and catechin. Protocatechuic acid is an antioxidant that also has inhibitory capacity against the PLA 2 of snake venoms [31]. Likewise, various isomers of catechin have been studied because of their inhibitory activity of PLA 2 present in snake venoms [12,32].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, given the promising bioactivity of fraction F5, in the characterization of the major compounds by GC-MS it was relevant to find two phenolic compounds in the derivatized fraction F5, namely protocatechuic acid, and catechin. Protocatechuic acid is an antioxidant that also has inhibitory capacity against the PLA 2 of snake venoms [31]. Likewise, various isomers of catechin have been studied because of their inhibitory activity of PLA 2 present in snake venoms [12,32].…”
Section: Discussionmentioning
confidence: 99%
“…This effect was attributed to complexation and chelation among the venom proteins and the phenolic contents of the extract. According to the authors, the Camellia sinensis extract also inhibited phospholipase A 2 , proteases, hyaluronidase and L-amino acid oxidase by in vitro neutralization and the hemorrhagic and the dermonecrotic activities of the venoms in vivo (Pithayanukul et al, 2010). Satoh et al (2002 a,b) reported the protective effect of thearubigin from black tea extract against the neuromuscular blockade caused by botulin neurotoxins and tetanus toxin in synaptosomal membrane preparations.…”
Section: Pharmacology 578mentioning
confidence: 99%
“…This experimental model has been traditionally used for the pharmacological characterization of snake venoms, and the association between C. sinensis and snake venoms was a natural consequence. Thus, results showing the inhibitory effect of tea polyphenols on local tissue damage induced by snake venoms (Pithayanukul et al, 2010), and the inhibitory effect of Camellia sinensis leaves extracts against the neuromuscular blockade of Crotalus durissus terrificus venom (de Jesus Reis Rosa et al, 2010) were recently published. Here, using the same experimental procedure, the antivenom property of Camellia sinensis leaves extract was assayed against Bothrops jararacussu venom and its main myotoxin, bothropstoxin-I.…”
mentioning
confidence: 99%
“…Another valued property is their anti-inflammatory activity which is correlated with the blockage of the arachidonic acid transformation pathway (Ferrandiz and Alcaraz, 1991). Flavonoids are known inhibitors of many enzymes including thyroperoxidase deiodinases (Ferreira et al, 2002), and hyaluronidases (Pithayanukul et al, 2010). Because of the interactions with the cardiovascular system, some flavonoids are used as varice, extravasation and arteriosclerosis prevention agents (Vasanthi et al, 2012).…”
Section: Flavonoidsmentioning
confidence: 99%